2023
DOI: 10.1080/14756366.2023.2241674
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of hexahydroquinoline as anticancer scaffold targeting inhibition of wild and mutants EGFR (EGFR WT , EGFR T790M , and EGFR L858R )

Mahmoud G. Abo Al-Hamd,
Haytham O. Tawfik,
Omeima Abdullah
et al.

Abstract: Hexahydroquinoline (HHQ) scaffold was constructed and recruited for development of new series of anticancer agents. Thirty-two new compounds were synthesised where x-ray crystallography was performed to confirm enantiomerism. Thirteen compounds showed moderate to good activity against NCI 60 cancer cell lines, with GI % mean up to 74% for 10c . Expending erlotinib as a reference drug, target compounds were verified for their inhibiting activities against EGFR WT , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…A yellow prism crystal of C 22 H 18 FN 3 O 3 S was attached to a glass fiber with approximate measurements of 0.300 × 0.200 × 0.200 mm. All measurements were performed using graphite monochromated Mo–Kα radiation on a Rigaku R-AXIS RAPID diffractometer. , Compound 5e ’s crystallographic information (CCDC deposition number 2298601) was submitted to the Cambridge Crystallographic Data Center.…”
Section: Methodsmentioning
confidence: 99%
“…A yellow prism crystal of C 22 H 18 FN 3 O 3 S was attached to a glass fiber with approximate measurements of 0.300 × 0.200 × 0.200 mm. All measurements were performed using graphite monochromated Mo–Kα radiation on a Rigaku R-AXIS RAPID diffractometer. , Compound 5e ’s crystallographic information (CCDC deposition number 2298601) was submitted to the Cambridge Crystallographic Data Center.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that these compounds are effective in cancer-related inflammatory pathways such as TGF-� (La ¨ngle et al, 2019). Additionally, they have been demonstrated to have inhibitory effects on receptors involved in cancer development, such as EGFR, or to reverse multi-drug resistance (Abo Al-Hamd et al, 2023;Shahraki et al, 2020).…”
Section: Chemical Contextmentioning
confidence: 99%